Issue Information. Issue 4 (7th December 2020) - Unknown
Abstract : Cover : In Bassiouni et al. (http://doi.org/10.1002/cpmo.84 ), the image shows frozen sections of the C57BL/6J mouse cochlea at p3. To demonstrate the "mouse‐on‐mouse" background, we omitted incubation with the primary antibody but incubated the sections only with a secondary antibody (goat anti‐mouse Alexa Fluor 488). Some slides were blocked with 5% normal goat serum for 30 min. Other slides underwent the same serum blocking step, followed by a second blocking step with an anti‐mouse‐IgG blocking reagent for 1 hr at RT. (A ) Using sole blocking with serum resulted in a strong background fluorescence signal, most prominently in the spiral limbus, and a lateral cochlear wall. A moderate signal was seen in the basilar membrane, intercellular borders, spiral lamina, and in the capillaries of the stria vascularis. (B ) Using double‐blocking resulted in no background fluorescence signal under identical exposure time and microscopy conditions. Scale: 20 µm.